Editorial: Education at school and in the family in the time of Covid-19 pandemic - Sieradzka-Baziur, Bożena (Horyzonty Wychowania, 2021)
The pandemic of the infectious COVID-19 disease caused by the SARS-CoV-2 coronavirus, which began as an epidemic in November 2019 in the Chinese city of Wuhan, has influenced the functioning of the world, and has had a huge impact on education in individual countries. It forced the closure of schools and universities around the world and the introduction of remote education wherever possible. Thanks to modern IT technologies, the family home of pupils and students has become the primary place for teaching them remotely by teaching institutions. The teachers started teaching their pupils, transforming the family home into their place of work. Educational institutions and family members in which the educational, upbringing and caring processes took place and are still continued, faced many challenges. People participating in educational processes in family homes played the roles of a pupil (student), teacher or support person, observing these processes, and they could act not only in one of these roles, e.g. being both a parent and a teacher, a student and a parent, etc. Numerous scientific publications mention the interpersonal, competence and material conditions of remote education in conditions of forced isolation, during which the weaknesses and strength of Polish families, schools and universities were revealed. The positive aspects of remote education include an increase in digital competences as well as a discussion on further directions for the development of remote education in Poland, expansion of the IT infrastructure, equipping some students with the necessary electronic equipment, and the development of institutions dealing with remote learning. Remote education also has its dark side. This type of teaching conducted as exclusive does not sufficiently satisfy the need for belonging, which is one of the essential needs of the human being. The current methods and means of remote education are still in the process of being developed. For a variety of reasons, some remote education participants have experienced digital exclusion, and the limitations of remote education have had a negative impact on the level of acquired knowledge. Teaching and learning at home had a negative impact on the physical and mental health of students and teachers. The articles in this volume of “Horyzonty Wychowania” contribute to a wide range of research work on distance learning at school and in the family in the time of the Covid‑19 pandemic. We cordially invite you to discuss and reflect on the issues presented by the authors. Bożena Sieradzka-Baziur theme issue editor